Analysis of Relationship Between Foot Morphology and Static Balance in Female Athletes - Nihat Sarıalioğlu (Türk Spor ve Egzersiz Dergisi)
This study was conducted to investigate the relationship between the morphological structure of the foot and female athletes’ static balance levels. 51 female athletes with an average age of 22.25±0.38 years participated in the research. The foot morphology was evaluated in 4 parameters. Balance scores were evaluated in 8 parameters. Spearman and Pearson correlation tests were used to determine the relationship between parameters (p lt;05). According to the results, it was observed that in the right foot there was a negative significant correlation between foot index (FI) parameter and standard deviation of forward and backward sway (FBSD), average forward backward speed (AFBS), used perimeter (P), used area (A) balance scores. In the left foot, there was a positive correlation between the FI parameter and the pressure to the average central y axis (COPY) balance score, and a negative significant relationship between the FI parameter and the FBSD and AFBS balance scores. It was determined that there was a positive significant correlation between the Chippaux Smirak index (CSI) and Staheli index (SI) parameters of both feet and the pressure to the average central x point (COPX) balance score. The results can be interpreted that the anatomical structure of the foot is important in the static balance characteristics of athletes.